The Impact of a High/Low Fulcrum Rotating Balance Platform on Standing Postural Stability in Healthy Young Adults - Rosario, Martin G; Bowman, Carley; Versemann, Abigail; Heistand, Daniel (Journal of Sports Research, 2021)
Back or lower limb pathology may interfere with standing balance. Knowing the impact of high and low fulcrum balance platforms on tracking rotational activities could tailor stability training interventions. Purpose: To determine the influence of a low and high fulcrum balance platform combined with tracking tasks on postural sway while standing. Method: Twenty-five participants performed seven activities at two difficulty levels. The total sway area and medial-lateral (ML) and anterior-posterior (AP) sway direction, velocity, and distance were measured during balance activities with various tracking platforms with a fixed middle fulcrum. Results: MANOVA revealed that postural sway area (m^2/s^4) with a high fulcrum decreased in front to back, rear twist, and front twist (p = 0.05) balance activities. The Mean velocity (m/s) analysis showed that tasks with a high fulcrum elicited slower velocities in the ML direction than those with low fulcrum activity (p < 0.05). Velocity also had more significant differences between tasks than any other variable (p < or =.05). Sway on the high fulcrum platform showed a longer length or distance in the AP direction (p < 0.05). Conclusion: Young, healthy adults, adjusted to more challenging balance tasks, such as when BoS is elevated, or rotational perturbations are added, by increasing sway velocity in the ML direction and sway distance in the AP direction. Clinicians and researchers should consider the height of the balance platforms and add rotation disturbances to increase the balance system’s demands on different populations and pathologies.